Avaliação do processo de fermentação alcoólica em condições de altas concentrações de açúcares empregando leveduras de características floculantes - Brandão, Ana Carolina Tolentino (2019)
With the expansion of ethanol production in Brazilian distilleries, the incorporation of new technologies in the fermentation process has become essential in order to raise ethanol production potential and minimize the impacts generated, especially with regard to the reduction of vinasse volume. One technology that has attracted a lot of interest is Very High Gravity (VHG) fermentation, which involves the preparation of media with high concentrations of sugars. This technology has advantages over conventional approaches, musts with high alcohol content, minimization of production costs and reduction of vinasse volume. In this context, the objective of this work was to study the influence of temperature, sugar concentration and cell concentration on the batch reactor using Saccharomyces cerevisiae yeast strain C2/00 using a Central Compound Designation (CCD). The conditions adopted by CCD were: temperature (21-29°C), sugar concentration (240-320g/L) and cell concentration (12-30%v/v). The tests were carried out in shaker under temperature and rotation control, using synthetic medium sugar and yeast extract. The fermentations were monitored over time by the measurements of sugars and ethanol concentrations during 24 hours of fermentation. And cell viability was analyzed at the beginning and end of the fermentation. The ranges of the variables analyzed in the CCD that maximized yield, cell concentration and productivity responses and minimized the residual sugar response were temperature of 25-29°C, initial TRS concentration of 260-310 g/L and cellular concentration of 22-30% (v/v). It was observed that using the conditions generated by Statistica® for the validation, the models obtained by the surfaces of responses and contour curves, presented good reproducibility, since the experimental results were similar to the predicted results. The batch alcoholic fermentations in a fed under VHG conditions provided alcoholic contents of 17.64-18.54°GL and yields of 90.78-94.12% satisfactory when compared to the conventional process and other authors. The efficiency of the batch process fed with cell reuse remained relatively constant, and in the 1st fermentation the viability was 84.85% while the 2nd fermentation reusing the 1st cells was 88.18%, evidencing the possibility of reuse in successive cycles in fermentations with high alcohol content